A brief review on the mechanical properties of Carbon nanotube reinforced polymer composites. (2020) - Pratyush Behera, Rohit; Rawat, Prashant; Kumar Tiwari, Santosh; Kumar Singh, Kalyan
Abstract: Carbon nanotubes (CNTs) have been in use for a long time for preparation of polymer composites due their excellent mechanical, thermal, electrical, physical properties etc. Many industries including automobile, aerospace, sports and marine industries have been using CNTs as a multi-functional material for improving the overall properties of their prepared composites with a small amount of loading value. In this review, we list the mechanical properties of nanotube reinforced polymer composites with processes used in order to find the ideal approach to the recently used methods for exploiting maximum properties of CNTs